Effects of Emotional Images on Cardiovascular Responses in Males with Coronary Artery Disease and in Healthy Males: The Role of Sensation Seeking - Ezzati, Davoud; Hashemi Nosrat Abad, Touraj; Babapour Kheiroddin, Jalil; Sabourimoghaddam, Hasan; Taban Sadeghi, Mohammadreza; Namdar, Hossein; Sadeghi, Babak; Hakimi, Masoumeh (International Journal of Cardiovascular Practice, 2018)
Introduction: Individuals exposed to certain types of images, based on their personality features, experience different emotional states and physiological responses. The present study addressed the effects of stressful and pleasant stimuli on blood pressure and heart rate in male patients with coronary problems and healthy males based on sensation seeking levels.Methods: One hundred and seventy eight male patients with coronary artery diseases referred to Madani Heart Hospital, Tabriz, Iran; and 185 healthy male subjects completed the Sensation Seeking Scale-form V (SSS-V). After obtaining acceptable scores, 100 patients and 100 healthy males were classified in four groups: high sensation seeker patients, low sensation seeker patients, high sensation seeker healthy subjects, and low sensation seeker healthy subjects (each group with 50 samples aged 30-49). First, blood pressures and heart rates were recorded before stimulus induction. Then, the participants were exposed to stressor pictures. After 15 minutes of relaxation, and a cognitive task, the participants were exposed to pleasant pictures. The blood pressure and heart rate were recorded after presenting the two stimuli.Results: High sensation seeker patients achieved lower scores in diastolic blood pressure in comparison with low sensation seeker patients after presenting the stressful stimulus, and healthy high sensation seekers achieved lower scores in systolic blood pressure in comparison with healthy low sensation seekers presented with pleasant stimulus.Conclusions: Low sensation seeker patients experienced negative emotions more than high sensation seeker patients. Therefore, the role of induced mood states may be important in relation to physical health.